Предмет: Алгебра,
автор: katiekyshenko
как решить а) (х - 1)(х - 3) = (х - 2)(х + 3); б) (2y - 1)(1 - y) + (y + 1)(2y - 3) = 0; в) (0,5х - 3,5)(6х + 2) + 30х = 3х(х - 3) - 26;
Ответы
Автор ответа:
0
а) x^2-3x-x+3=x^2+3x-2x-6
-4x+3=x-6
-5x=-9
x=9/5
б) 2y-2y^2-1+y+2y^2-3y+2y-3=0
2y-4=0
2y=4
y=2
в) 3x^2+x-21x-7+30x=3x^2-9x-26
10x-7=-9x-26
19x=-19
x=-1
-4x+3=x-6
-5x=-9
x=9/5
б) 2y-2y^2-1+y+2y^2-3y+2y-3=0
2y-4=0
2y=4
y=2
в) 3x^2+x-21x-7+30x=3x^2-9x-26
10x-7=-9x-26
19x=-19
x=-1
Похожие вопросы
Предмет: География,
автор: sogoryunova
Предмет: Другие предметы,
автор: trufznastya
Предмет: Русский язык,
автор: Аноним
Предмет: Литература,
автор: ognitoelvina
Предмет: Алгебра,
автор: GrandDoto